Plagiarism: Ke Garne ? - Editor, The (Himalayan Journal of Sciences, 2007)
It wasn’t your typical fish story. This wasn’t a fisherman exaggerating the size of the one that got away — it was a case of massive plagiarism. Fortunately, HJS editors caught it before the story went to print, but we paid a price in time, money, and goodwill. Now we have to think seriously about what we can do to protect ourselves from intellectual dishonesty. We invite your suggestions and your collaboration. Himalayan Journal of Sciences 3(5) 2005 p.7